2021
DOI: 10.26442/22217185.2021.1.200768
|View full text |Cite
|
Sign up to set email alerts
|

The role of markers of endothelial dysfunction, oxidative and cellular stress in the prediction of myocardial infarction in comorbid patients with stable coronary heart disease

Abstract: Aim. To study the role of markers of endothelial dysfunction, oxidative and cellular stress in the prediction of myocardial infarction (MI) in comorbid patients with stable coronary heart disease (CHD). Material and methods. The study involved 336 patients with a diagnosis of CHD. The presence of CHD was confirmed by diagnostic coronary angiography with the calculation of the Gensini index. All patients were divided into 2 groups: group 1288 patients without a history of MI, group 248 patients with a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have demonstrated the beneficial effects of exercise on the prognosis of patients with CHD (24). It is widely accepted that oxidative stress and inflammation are key factors in the progression and pathogenesis of CHD (25). As the main indicators regulating the balance between oxidation and antioxidation in the body, MDA and SOD play an important role in inhibiting atherosclerosis (26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial effects of exercise on the prognosis of patients with CHD (24). It is widely accepted that oxidative stress and inflammation are key factors in the progression and pathogenesis of CHD (25). As the main indicators regulating the balance between oxidation and antioxidation in the body, MDA and SOD play an important role in inhibiting atherosclerosis (26).…”
Section: Discussionmentioning
confidence: 99%